Derive a formula for Summation n i=1 i3 by using a telescoping sum with terms f(i)=i2
i⁴ - (i-1)⁴ = i⁴ - (i⁴ - 4i³ + 6i² - 4i + 1)
=> i⁴ - (i-1)⁴ = i⁴ - i⁴ + 4i³ - 6i² + 4i - 1
=> i⁴ - (i-1)⁴ = 4i³ - 6i² + 4i - 1
Taking sum over i = 1 to n
"\\sum_{i=1}^{n}" {i⁴ - (i-1)⁴ }= "\\sum_{i=1}^{n}"{4i³- 6i²+4i - 1}
=> n⁴ - 0⁴ = "\\sum_{i=1}^{n}4i\u00b3-\\sum_{i=1}^{n} 6i\u00b2 +\\sum_{i=1}^{n} 4i - \\sum_{i=1}^{n} 1"
=> n⁴ = "4\\sum_{i=1}^{n}i\u00b3-6\\sum_{i=1}^{n} i\u00b2 +4\\sum_{i=1}^{n} i - \\sum_{i=1}^{n} 1"
=> n⁴ = "4\\sum_{i=1}^{n}i\u00b3-" 6."\\frac{n(n+1)(2n+1)}{6}" + "4.\\frac{n(n+1)}{2}-n"
=> n⁴ = "4\\sum_{i=1}^{n}i\u00b3" - n(n+1)(2n+1) + 2n(n+1) - n
=> "4\\sum_{i=1}^{n}i\u00b3" = n⁴ + n(n+1)(2n+1) - 2n(n+1) + n
=> "4\\sum_{i=1}^{n}i\u00b3" = n⁴ + 2n³ + 3n² + n - 2n² - 2n + n
=> "4\\sum_{i=1}^{n}i\u00b3" = n⁴ + 2n³ + n²
=> "4\\sum_{i=1}^{n}i\u00b3" = (n² + n)²
=> "4\\sum_{i=1}^{n}i\u00b3" = {n(n+1)}²
=> "\\sum_{i=1}^{n}i\u00b3" = "\\frac{ {n\u00b2(n+1)}\u00b2}{4}"
=> "\\sum_{i=1}^{n}i\u00b3 =" "[\\frac{n(n+1)}{2}]\u00b2"
Comments
Leave a comment